ANALISIS KINERJA AGROINDUSTRI CRUDE COCONUT OIL (CCO) PADA IKRT “SUMBER REZEKI” DI DESA TINABOGAN KECAMATAN DONDO KABUPATEN TOLITOLI - Mulkiah Amal Basri; Asriani Hasanuddin; Lien Damayanti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
This study is a case study on the performance of crude coconut oil (CCO) agroindustry business run by Tinabogan Village community through a small household industrygroup SumberRezeki which is one of the developments of integrated coconut industry byTolitolidistrict government of Central Sulawesi. This study aimed to analyze the two-year performance of the group "SumberRezeki" in Tinabogan village using financial analysis. The research used profitability ratio and liquidity ratio methods. The profitability ratio usedwas the ratio of gross profit margin (GPM), net profit margin (NPM) ratio, return on investment (ROI), and return on equity (ROE) ratio. The liquidity ratio used wascurrent ratio (CR), quick ratio (QR) and cash ratio (CR). The results of the analysis showed that the overall profitability ratio of the business is efficient indicating that it is in a good performance interpretation. Although there is a decrease in ROI and ROE generated in time series of 2015 and 2016, the ratio of industry is still above the average suggesting that the business performance is good. Similarly, the liquidity ratio is liquid meaning that the business is able to pay its short-term debt on time. Keywords:Agroindustry, liquidity ratio, performance and profitability ratio.